Prevention Cost Components Priorities for Urban Rail Infrastructure Projects - Izatul Farrita Mohd Kamar; Che Ahmad, Asmalia; Mohd Derus, Mohmad (International Journal of Sustainable Construction Engineering and Technology, 2022)
The Mass Rapid Transit (MRT) and the Light Rail Transit (LRT) have been established as the largest transport infrastructure projects in Malaysia and cost over RM40 billion. Due to the vigorous development of both projects, accidents at project sites have caused fatalities, serious injuries, and damage to properties. Many accidents have occurred during the operation of rail. In Malaysia, the latest rail accident occurred on 24th May 2021 had injured 200 people when two coaches on the Kelana Jaya LRT line collided in the capital Kuala Lumpur. Rail accidents create significant economic impacts on the country, stakeholders, and society. Studies on the prevention costs during the pre-construction stage of a project are scarce and have mainly focused on the financial losses or accident costs incurred by the contractor and victim. Among the limitations of the existing safety and health cost models is that they do not include the costs incurred by the client for the safety prevention activities. Therefore, this research aims to study the types of prevention cost components that must be the priorities for urban rail infrastructure projects. The data analysed in this study was obtained from a total of eight (8) projects involved in the MRT 1 (SBK Line) and ten (10) projects involved in the MRT 2 (SPP Line). The prevention cost components priorities were determined by the coefficient of variation (CV) percentage. The finding shows ten (10) prevention cost components, and nineteen (19) prevention cost items were allocated during the pre-construction phase. The cost components were the Plant Costs, OSH Management Costs, Housekeeping Costs, Special Work Condition Costs, Evaluation and Monitoring Costs, Emergency Response Costs, Electrical Work Costs, PPE and Training Costs, Facilities on Site Costs, and Insurance Costs. This study finds out that all these prevention cost components are important to prevent accidents for the employees when carrying out work on-site. Therefore, clients should consider the availability of these cost components in the planning and preparation phases of an urban rail infrastructure project. Thus, the most logical amount of prevention cost components can be achieved in the future project and creating the awareness of these costs to the clients.